Occurrence of black spot disease induced by Posthodiplostomum cuticola (Nordmann, 1832) (Digenea: Diplostomatidae) in endemic and native fish of Turkey: seven new host records - INNAL, D.; ÖZDEMIR, F.; STAVRESCU-BEDIVAN, M.M.; OZMEN, O.; ÖZTURK, M.O. (Journal of the Hellenic Veterinary Medical Society, 2020)
This study was conducted to determine parasite infection with Posthodiplostomum cuticola in eight fish species collected from five Rivers Basins of Turkey (Aras, Çoruh, Sakarya, Marmara and Susurluk River Basins). Five of eight fish species are endemic to Turkey. The highest values of prevalence and mean intensity (60.87%; 4.86) of cysts with metacercaria of P. cuticola were recorded in Alburnus filippii, a native fish species in Ağıl Creek. At the gross examination numerous black lesions were observed at the skin of the fishes. Microscopically black-spot disease was revealed by melanin pigmentation and atrophy of fish muscles in lesioned areas. Parasites were covered by thing connective tissue capsule. Alburnus escherichii, Alburnus filippii, Capoeta tinca, Chondrostoma angorense, Chondrostoma colchicum, Squalius pursakensis and Squalius turcicus were found as new host records for P. cuticola.